Political Justice : The Use of Legal Procedure for Political Ends - Kirchheimer, Otto (Princeton, NJ : Princeton University Press, 2015)
How have regimes used the agencies of criminal justice for their own purposes? What characterizes the linkage of politics and justice? Drawing on a wealth of foreign and domestic source material, Otto Kirchheimer examines systematically the structure of state protection, the nature of a strictly "political" trial, including the trial by fiat of the successor regime, and the forms of legal repression that states have used against political organizations. He analyzes the Nuremberg trials, the Communist purge trials, and a number of Smith Act trials. In two highly original chapters he also explores the political and judicial nature of asylum and clemency. This study of the uneasy balance between abstract justice and political expediency is a contribution to constitutional and criminal law, political science, and social psychology.Originally published in 1961.The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.
Frontmatter -- PREFACE -- CONTENTS -- CHAPTER I. INTRODUCTION -- PART ONE. Political Justice: Cases, Causes, Methods -- CHAPTER II. CHANGES IN THE STRUCTURE OF STATE PROTECTION -- CHAPTER III. THE POLITICAL TRIAL -- CHAPTER IV. LEGAL REPRESSION OF POLITICAL ORGANIZATIONS -- PART TWO. The Judge, the Defendant, and the State -- CHAPTER V. CONDITIONS OF JUDICIAL ACTION -- CHAPTER VI. THE DEFENDANT, HIS LAWYER, AND THE COURT -- CHAPTER VII. "DEMOCRATIC CENTRALISM" AND POLITICAL INTEGRATION OF THE JUDICIARY -- CHAPTER VIII. TRIAL BY FIAT OF THE SUCCESSOR REGIME -- PART THREE. Political Justice Modified: Asylum and Clemency -- CHAPTER IX. ASYLUM -- CHAPTER X. THE QUALITY OF MERCY -- CHAPTER XI. SUMMING UP -- APPENDIX A. THE ROMAN EMPIRE AND THE CHRISTIANS -- APPENDIX B. GUILLAUME DU VAIR: THE CASE OF T H E SUCCESSFUL LOYALTY SHIFT -- INDEX
Mode of access: Internet via World Wide Web.
In English.
Description based on online resource; title from PDF title page (publisher's Web site, viewed 08. Jul 2019)
Keywords: Law -- Political aspects; POLITICAL SCIENCE / History & Theory